John Howard, weapons of mass destruction and the public’s right to know - Richard Mills (Asia Pacific Network, 2008)
In March 2003, Australia went to war in Iraq to find and remove Saddam Hussein’s weapons of mass destruction (WMD).  None were found.  An Australian Parliamentary Committee concluded: The case made by the government was that Iraq possessed WMD on large quantities  and posed a grave and unacceptable threat to the region and the world, particularly as there was a danger that Iraq's WMD might be passed to terrorist organisations. This is not the picture that emerges from an examination of the assessments provided to the Commmittee by the Australian Office of National Assessments (ONA) and the Defence Intelligence Organisation (DIO).